Digital Economy - This is the Economy of the Current Times - ugli, Sharobiddinov Ahrorbek Qosimjon (Research Parks Publishers, 2023)
Currently, in many developed countries, the digital economy and the factors of their development have a significant impact, and the digital economy plays an important role in the life of society. The article describes the definitions and different approaches to the category of